snoRNA nuclear import and potential for cotranscriptional function in pre-rRNA processing. - Peculis, B A (2001)
Several snoRNAs are essential for the sequence of cleavage events required to produce the mature forms of 18S, 5.8S, and 28S rRNA from the large precursor molecule. In the absence of U22, mature 18S rRNA fails to accumulate; U8 snoRNA is essential for accumulation of both 5.8S and 28S rRNA. The mechanisms by which snoRNAs facilitate these cleavage events is not known and might include direct cleavage or assisting the rate or efficiency of ribosome assembly. To learn more about the mechanisms of snoRNA-mediated pre-rRNA processing, an examination of the kinetics of pre-rRNA processing in Xenopus oocytes was undertaken. Correct pre-rRNA processing can be restored in snoRNA-depleted oocytes following cytoplasmic injection of the corresponding in vitro-synthesized snoRNA. Analysis of the kinetics of pre-rRNA processing in these snoRNA-rescue experiments demonstrated that the rate of accumulation of mature rRNAs was slower than that seen in untreated oocytes. The snoRNAs were imported into the nucleus at a rate and overall efficiency less than that of U1 snRNA, used as a control for import. However, sufficient levels of snoRNA were present in the nucleus to yield a functional phenotype (rescue of rRNA processing) several hours before the snoRNAs were directly detectable in the nucleus via autoradiography. This indicated that very low amounts of the snoRNA in the nucleus were sufficient for rescue. Finally, transcriptional inhibitors were used to separate transcription and processing. Failure to rescue snoRNA-mediated processing of pre-accumulated precursors is consistent with a scenario in which U8 and U22 must be present during transcription of pre-rRNA.